Cancer immunotherapy-associated hypophysitis - Castillero Rodríguez, Franklin Agustín (2019)
The advances in cancer therapy have included the development of drugs that inhibit immune checkpoint ligands. Two types of immune checkpoint inhibitors, both antibodies that target CTLA-4 and PD-1, have been approved for its use in NSCLC and melanoma as first-line or second-line therapy. Sadly, not desirable consequences of immunotherapy are immune-related adverse events. immune-related hypophysitis is the most common endocrine adverse event after thyroid disfunction. The particularity of endocrine immunerelated adverse events is their non-reversibility, with incidence and prevalence destined to increase in the coming years, particularly if this form of therapy is used in the future for earlier stages of cancer. Therefore, hypophysitis represents a challenge for the physician, sometimes occurring without specific symptomatology and which should be considered for clinical management. In this review, we describe the current data regarding the pathophysiology and management for immune-related hypophysitis.